EVALUACIÓN DE LAS MEDIDAS DE GRUPA Y MUSLO DE LA CRÍA Y UBRE DE LA MADRE COMO INDICADORES FENOTÍPICOS EN LA SELECCIÓN TEMPRANA DE LLAMAS (Lama glama) PARA CARNE. - Zea M, Otto (2007)
A flock of 82 llamas with their calves was used to evaluate the hip area and thigh volume of the young and the size of the mammary gland of the dam as possible indicators for early selection of llamas for meat production. In the young, the development of hips and thighs at 2, 8, and 15 months of age and the correlation of these measurements with body weight and chest circumference were evaluated, whereas in the dams, the relation between size of the mammary gland and body weight at weaning of the calf was evaluated. Size of hip was calculated as a geometric figure using the Autocad software, and the size of the thigh was expressed as the volume of a truncated cone. The increase of body weight (65.3%), hip area (51.5%), thigh volume (53.2%) were significantly higher (p<0.05) than the increase in chest circumference (32.9%). Animals were distributed into two groups according to hip area at 2 months of age and the differences in biometric measurements were kept at 8 and 15 months of age. These differences were also kept in the other variables (thigh volume, chest circumference and body weight), indicating that body development was similar in both groups. Correlation coefficients between hip area, thigh volume, chest circumference, body weight and age were significant (p<0.001). Coefficient correlations between udder measurements and body weight at weaning were small, with the exception of distance among anterior udder teats and body weight at weaning (0.46). Results suggested that hip area and thigh volume can be used as genetic indicators for early selection of young animals for meat production as they keep a high and significant correlation with body weight and chest circumference.